A study protocol of the adaptation and evaluation by means of a cluster-RCT of an integrated workplace health promotion program based on a European good practice - Denise J. M. Smit; Sandra H. van Oostrom; Josephine A. Engels; Allard J. van der Beek; Karin I. Proper (BMC, 2022)
Abstract Background An integrated workplace health promotion program (WHPP) which targets multiple lifestyle factors at different levels (individual and organizational) is potentially more effective than a single component WHPP. The aim of this study is to describe the protocol of a study to tailor a European good practice of such an integral approach to the Dutch context and to evaluate its effectiveness and implementation. Methods This study consists of two components. First, the five steps of the Map of Adaptation Process (MAP) will be followed to tailor the Lombardy WHP to the Dutch context. Both the employers and employees will be actively involved in this process. Second, the effectiveness of the integrated Dutch WHPP will be evaluated in a clustered randomized controlled trial (C-RCT) with measurements at baseline, 6 months and 12 months. Clusters will be composed based on working locations or units - dependent on the organization's structure and randomization within each organization takes place after baseline measurements. Primary outcome will be a combined lifestyle score. Secondary outcomes will be the separate lifestyle behaviors targeted, stress, work-life balance, need for recovery, general health, and well-being. Simultaneously, a process evaluation will be conducted. The study population will consist of employees from multiple organizations in different industry sectors. Organizations in the intervention condition will receive the integrated Dutch WHPP during 12 months, consisting of an implementation plan and a catalogue with activities for multiple lifestyle themes on various domains: 1) screening and support; 2) information and education; 3) adjustments in the social, digital or physical environment; and 4) policy. Discussion The MAP approach provides an appropriate framework to systematically adapt an existing WHPP to the Dutch context, involving both employers and employees and retaining the core elements, i.e. the catalogue with evidence-based activities on multiple lifestyle themes and domains enabling an integrated approach. The following process and effect evaluation will contribute to further insight in the actual implementation and effectiveness of the integrated WHP approach. Trial registration NTR (trialregister.nl ), NL9526. Registered on 3 June 2021.